Cryopreservation of fish embryos: insights from Cyprinodon variegatus - González, Ramiro; Rocha, Francisco; Paredes, Estefanía (Problems of Cryobiology and Cryomedicine, 2025)
Probl Cryobiol Cryomed 2025; 35(4):232